Disclosure of Environmental Accounting, Institutional Ownership, and Corporate Social Responsibility on Company Value Moderated by Financial Performance - Malindha, Tasya Rizki; Permatasari, Ditya (Fakultas Ekonomi, UIN Maliki Malang, 2024)
This study aims to find out that the disclosure of environmental accounting, institutional ownership, and Corporate Social Responsibility moderated by financial performance has an effect on the company's value. The population in this study is mining sector companies listed on the Indonesia Stock Exchange from 2019 to 2022. This study uses a quantitative approach, using multiple linear regression analysis techniques and Moderated Analysis Regression. The results of this study show that the disclosure of environmental accounting and institutional ownership has an influence on company value while corporate social responsibility has no effect on company value. This research will provide insight into the function of corporate governance in companies, especially in environmental cost management, the importance of institutional ownership percentages and corporate social responsibility in increasing company value.